Foreign Intervention and Threats to Sovereignty in Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
Foreign intervention in a country's domestic affairs is often a controversial issue in international relations. Intervention can occur in military, economic, or diplomatic forms on the grounds of humanity, democracy, or peace. However, intervention is often considered to violate the principle of state sovereignty and become a tool of great power hegemony.